Hypoxia downregulates the expression of activating receptors involved in NK‐cell‐mediated target cell killing without affecting ADCC. Issue 10 (5th August 2013) - Balsamo, Mirna; Manzini, Claudia; Pietra, Gabriella; Raggi, Federica; Blengio, Fabiola; Mingari, Maria Cristina; Varesio, Luigi; Moretta, Lorenzo; Bosco, Maria Carla; Vitale, Massimo
<x xml:space="preserve">Abstract</x> In certain infection sites or tumor tissues, the disruption of homeostasis can give rise to a hypoxic microenvironment, which, in turn, can alter the function of different immune cell types and favor the progression of the disease. Natural killer (NK) cells are directly involved in the elimination of virus‐infected or transformed cells, however it is unknown whether their function is affected by hypoxia or not. In this study, we show that NK cells adapt to a hypoxic environment by upregulating the hypoxia‐inducible factor 1α. However, NK cells lose their ability to upregulate the surface expression of the major activating NK‐cell receptors (NKp46, NKp30, NKp44, and NKG2D) in response to IL‐2 (or other activating cytokines, including IL‐15, IL‐12, and IL‐21). These altered phenotypic features correlate with reduced responses to triggering signals resulting in impaired capability of killing infected or tumor target cells. Remarkably, hypoxia does not significantly alter the surface density and the triggering function of the Fc‐γ receptor CD16, thus allowing NK cells to maintain their capability of killing target cells via antibody‐dependent cellular cytotoxicity. This finding offers an important clue for exploitation of NK cell in antibody‐based immunotherapy of cancer.